Aplicação de técnicas eletroquímicas no estudo da dissolução oxidativa da covelita (CuS) por Thiobacillus ferrooxidans - Teixeira, Christiane Medina [UNESP] (2002)
Among the copper sulphides, chalcopyrite (CuFeS2), covellite (CuS) and chalcocite (Cu2S) are the most important source of minerals for copper mining industry. The acknowledge of behaviour of these sulphides related with bacterial leaching process are essential for optimization procedures. Despite of its importance, covellite has not deserved much interest of researchers regarding this matter. In this work it was studied the oxidation of covellite by the chemolithotrophic bacterium Thiobacillus ferrooxidans by using electrochemical techniques, such as open circuit potentials with the time and cyclic voltammetry. The experiments were carried out in acid medium (pH 1.8), containing or not Fe2+ as additional energy source, and in different periods of incubation; chemical controls were run in parallel. The results showed that a sulphur layer is formed spontaneously due the acid attack, covering the sulphide in the initial phase of incubation, blocking the sulphide oxidation. However, the bacterium was capable to oxidize this sulphur layer. In the presence of Fe2+ as supplemental energy source, the corrosion process was facilitated, because ocurred an indirect oxidation of covellite by Fe3+, which was produced by T. ferrooxidans oxidation of the Fe2+ added in the medium.